2021
DOI: 10.3390/cancers13195031
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of SPIO Injection for Sentinel Lymph Node Dissection in a Rat Model

Abstract: The magnetic technique, consisting of a magnetic tracer and a handheld magnetometer, is a promising alternative technique for sentinel lymph node dissection (SLND) and was shown to be non-inferior to the standard technique in terms of identification rates. In this study, injection characteristics (iron dose, dilution, time course and massaging) were evaluated to optimize magnetic tracer uptake in the sentinel lymph nodes (SLN) in a rat hindleg model. 202 successful SLNDs were performed. Iron uptake in the SLN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
3
2
0
Order By: Relevance
“…Although injection more than 24 h before surgery was shown to increase detection over peroperative or intraoperative administration, the optimal or maximum interval between SPIO administration and surgery still needs to be defined. It seems that extending the time before surgery allows increased SPIO concentration in the SLN, facilitating identification, a finding in line with experimental data 52 . Several studies 11 , 18 have reported on a time frame that extends up to 27 days in upfront SLNB.…”
Section: Discussionsupporting
confidence: 83%
“…Although injection more than 24 h before surgery was shown to increase detection over peroperative or intraoperative administration, the optimal or maximum interval between SPIO administration and surgery still needs to be defined. It seems that extending the time before surgery allows increased SPIO concentration in the SLN, facilitating identification, a finding in line with experimental data 52 . Several studies 11 , 18 have reported on a time frame that extends up to 27 days in upfront SLNB.…”
Section: Discussionsupporting
confidence: 83%
“…The magnetic fields of SLNs in the overall participants and in each group were linearly correlated with their iron content. These data corroborated a previous canine study [13] carried out with ferucarbotran and one with porcine models with another SPIO nanoparticle (Sienna+; Sysmex, Kobe, Japan) [17,18]. The canine study [13] was a preclinical study carried out in spontaneous tumor-bearing dogs.…”
Section: Discussionsupporting
confidence: 86%
“…These data corroborated a previous canine study [13] carried out with ferucarbotran and one with porcine models with another SPIO nanoparticle (Sienna+; Sysmex, Kobe, Japan) [17,18]. The canine study [13] was a preclinical study carried out in spontaneous tumor-bearing dogs. Ferucarbotran was shown to be non-inferior to dye in detection of SLNs on veterinary clinical cases.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast, the RI probe can detect the radiation beam directly from SLNs [39]. Peek et al investigated injection characteristics of the magnetic tracer on the rat model, proving that iron uptake appears to be proportional to the injection dose before reaching a plateau level [40]. This outcome suggests that each lymph node presents maximum magnetic particles load depending on the size and location of the SLN.…”
Section: Discussionmentioning
confidence: 99%